Conversational repair and human understanding - Hayashi, Makoto; Raymond, Geoffrey; Sidnell, Jack. (Cambridge, UK : Cambridge University Press, 2013)
'Humans are imperfect, and problems of speaking, hearing and understanding are pervasive in ordinary interaction. This book examines the way we'repair' and correct such problems as they arise in conversation and other forms of human interaction. The first book-length study of this topic, it brings together a team of scholars from the fields of anthropology, communication, linguistics and sociology to explore how speakers address problems in their own talk and that of others, and how the practices of repair are interwoven with non-verbal aspects of communication such as gaze and gesture, across a variety of languages. Specific chapters highlight intersections between repair and epistemics, repair and turn construction, and repair and action formation. Aimed at researchers and students in sociolinguistics, speech communication, conversation analysis, anthropology, linguistics, psychology and sociology, this book provides a state-of-the art review of conversational repair, while charting new directions for future study'--
1. Conversational repair and human understanding: an introduction / Makoto Hayashi, Geoffrey Raymond, and Jack Sidnell -- 2. Ten operations in self-initiated, same-turn repair / Emanuel A. Schegloff -- 3. Self-repair and action construction / Paul Drew, Traci Walker, and Richard Ogden -- 4. On the place of hesitating in delicate formulations: a turn -onstructional infrastructure for collaborative indiscretion / Gene H. Lerner -- 5. One question after another: same-turn repair in the formation of yes/no type initiating actions / Geoffrey Raymond and John Heritage -- 6. On the interactional import of self-repair in the courtroom / Tanya Romaniuk and Susan Ehrlich -- 7. Defensive mechanisms: I-mean prefaced utterances in complaint and other conversational sequences / Douglas W. Maynard -- 8. Availability as a trouble source in directive-response sequences / Mardi Kidwell -- 9. Epistemics, action formation, and other-initiation of repair: the case of partial questioning repeats / Jeffrey D. Robinson -- 10. Proffering insertable elements: a study of other-initiated repair in Japanese / Makoto Hayashi and Kaoru Hayano -- 11. Alternative, subsequent descriptions / Jack Sidnell and Rebecca Barnes -- 12. Huh? What?-- A first survey in 20 languages / N. J. Enfield, Mark Dingemanse, Julija Baranova, Joe Blythe, Penelope Brown, Tyko Dirksmeyer, Paul Drew, Simeon Floyd, Sonja Gipper, R{u2BF3}a Glad{u2BF4}tir, Gertie Hoymann, Kobin H. Kendrick, Stephen C. Levinson, Lilla Magyari, Elizabeth Manrique, Giovanni Rossi, Lila San Roque, and Francisco Torreira.
Includes bibliographical references and index.
Keywords: Conversation analysis; Speech acts (Linguistics).; Sociolinguistics; Social interaction